A model of locomotor-respiratory coupling in quadrupeds - Giuliodori, Mauricio Javier (2009)
Locomotion and respiration are not independent phenomena in running mammals because locomotion and respiration both rely on cyclic movements of the ribs, sternum, and associated musculature. Thus, constraints are imposed on locomotor and respiratory function by virtue of their linkage. Specifically, locomotion imposes mechanical constraints on breathing that require the respiratory cycle to be synchronized with gait. Thus, many mammals, including humans, synchronize respiration with the movement of the limbs during locomotion. For example, quadrupeds synchronize locomotor and respiratory cycles at a 1:1 ratio (stride/breath) over a wide range of speeds. Interestingly, quadrupeds maintain an almost constant stride frequency (and therefore respiratory frequency) at different speeds. To increase speed, quadrupeds lengthen their stride. Accordingly, to increase minute ventilation, quadrupeds must increase tidal volume since respiratory rate is coupled with stride frequency. We developed a simple, inexpensive, and easy to build model to demonstrate this concept. A model was chosen because models significantly enhance student understanding. Students are drawn into discussion by the power of learning that is associated with manipulating and thinking about objects. Building and using this model strengthen the concept that locomotor-respiratory coupling provides a basis for the appropriate matching of lung ventilation to running speed and metabolic power.